From Dakwa to Fatwa: the Linguistic Violence behind Preacher's Digital Narrative - Iqbal, Muhammad (Institut Agama Islam Negeri (IAIN) Kendari, 2023)
Although research on linguistic violence in fatwas has been extensively examined by Islamic law experts, there are still few lectures on YouTube that discuss linguistic violence in fatwas. The current study aims to examine linguistic violence perpetrated by preachers on social media in order to fill research gaps. This study employs an interpretative qualitative case study design. This study uses document analysis to collect data. To analyze the data, William C. Gay's (1998) theory is applied. The results of the study indicate that there are subtle, abusive, and gesture forms of linguistic violence in the fatwa. Language, ideology, and power relations (popularity) contribute to the occurrence of linguistic violence. The effects of linguistic violence on congregations, in general, are discord among interfaith adherents, blasphemy among adherents on social media, and constraints from certain circles to clarify apologies. At the conclusion of this investigation, the study's implications are discussed.